(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
There are various cave paintings, writings on a clay tablets, magical papyrus, ancient literature that can witness the presence of figurines and voodoo dolls in magical activities from the beginning of the humanity, in particular those found at archaeological sites that were made out of different materials: wax, wool, wood, clay, dough, or of bronze and lead later, sometimes with or without written magical symbols or names on them, sometimes as evil, angry demons with human faces, with eyes wide open and monstrous noses, with bodies broken in two, with heads and extremities turned backwards, sometimes burned, tied or drilled, found in boxes or chests buried under the ruins of old buildings, sanctuaries or sacred sites, in tombstones or thrown into deep holes, sunken under water, etc. In order to have an insight into the impact of magical figurines and voodoo dolls in the religious discourse from the ancient times until the New Age related to the superstitious particularism in the folk’s beliefs about the evil they have caused, that transfers into superstitious universalism at a global level throughout the historical ages, the subject of this paper has two objects: To show the level of impact these figurines and voodoo dolls had among the masses throughout the history, having in mind the folk’s beliefs about their magical powers only if used in specific time and place and set in a typical way on one hand. And on the other to show the possible rudiments when using magical dolls, also known in modern society as voodoo dolls, and the fear they cause among some of the people.